2013
DOI: 10.1007/s00167-013-2465-4
|View full text |Cite
|
Sign up to set email alerts
|

ACL reconstruction with physiological graft tension by intraoperative adjustment of the anteroposterior translation to the uninjured contralateral knee

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The optimal graft tension for ATT intraoperatively is a matter of debate. Using the same device as that in the present study (Rolimeter), Bastian et al 3 reported that anteroposterior translation in the operated knee increased further from intraoperative measurements. Moreover, up to 30% of patients demonstrated a side-to-side difference of at least 3 mm at a median follow-up of 5.3 years, even if anteroposterior translation of the operated knee was equivalent to that of the contralateral uninjured knee measured intraoperatively.…”
Section: Discussionmentioning
confidence: 52%
“…The optimal graft tension for ATT intraoperatively is a matter of debate. Using the same device as that in the present study (Rolimeter), Bastian et al 3 reported that anteroposterior translation in the operated knee increased further from intraoperative measurements. Moreover, up to 30% of patients demonstrated a side-to-side difference of at least 3 mm at a median follow-up of 5.3 years, even if anteroposterior translation of the operated knee was equivalent to that of the contralateral uninjured knee measured intraoperatively.…”
Section: Discussionmentioning
confidence: 52%
“…Patients with greater instability in the pivot-shift test have been reported to have higher risk for residual instability after ACL reconstruction at the time of surgery [ 13 ]. It has been proposed that intraoperative instability in the pivot-shift test after ACL reconstruction may worsen rather than improve during follow-up, because the anteroposterior translation has been reported to increased further [ 3 ]. Therefore, even a slight residual instability, detectable only by quantitative measurement, may be undesirable thus it is valuable that ALL reconstruction can improve this residual instability.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with criteria (2) and/or (3) were not included in this study. An arthroscopic procedure was performed through anteromedial, anterolateral, and medial accessory portals.…”
Section: Surgical Techniquementioning
confidence: 99%
“…45 On the other hand, the laxity-based tensioning protocol applies initial tension that is individualized for each patient by matching the laxity of the uninjured knee using an arthrometer. 5,14…”
mentioning
confidence: 99%
“…45 On the other hand, the laxitybased tensioning protocol applies initial tension that is individualized for each patient by matching the laxity of the uninjured knee using an arthrometer. 5,14 Several studies have compared the amount of initial tension of force-based protocols to determine the level that produces the best clinical outcomes. 23,40,50,54,56 However, the optimal amount of initial tension remains unclear, and there is variability in adopted tensioning protocols among surgeons.…”
mentioning
confidence: 99%